The impact of hepatic steatosis on outcomes of colorectal cancer patients with liver metastases: A systematic review and meta-analysis - Yang, Shengjie; Peng, Renze; Zhou, Leiming (Frontiers in Medicine, 2022)
Background It is unclear how hepatic steatosis impacts patient prognosis in the case of colorectal cancer with liver metastases (CRLM). The purpose of this review was to assess the effect of hepatic steatosis on patient survival and disease-free survival (DFS) in the case of CRLM. Methods We examined the databases of PubMed, CENTRAL, Embase, Google Scholar, and ScienceDirect for studies reporting outcomes of CRLM patients with and without hepatic steatosis. We performed a random-effects meta-analysis using multivariable adjusted hazard ratios (HR). Results Nine studies reporting data of a total of 14,197 patients were included. All patients had undergone surgical intervention. Pooled analysis of seven studies indicated that hepatic steatosis had no statistically significant impact on patient survival in CRLM (HR: 0.92 95% CI: 0.82, 1.04, I2 = 82%, p = 0.18). Specifically, we noted that there was a statistically significant improvement in cancer-specific survival amongst patients with hepatic steatosis (two studies; HR: 0.85 95% CI: 0.76, 0.95, I2 = 41%, p = 0.005) while there was no difference in overall survival (five studies; HR: 0.97 95% CI: 0.83, 1.13, I2 = 78%, p = 0.68). On meta-analysis of four studies, we noted that the presence of hepatic steatosis resulted in statistically significant reduced DFS in patients with CRLM (HR: 1.32 95% CI: 1.08, 1.62, I2 = 67%, p = 0.007). Conclusion The presence of hepatic steatosis may not influence patient survival in CRLM. However, scarce data is suggestive of poor DFS in CRLM patients with hepatic steatosis. Further prospective studies taking into account different confounding variables are needed to better assess the effect of hepatic steatosis on outcomes of CRLM. Systematic review registration [https://www.crd.york.ac.uk/prospero/#searchadvanced], identifier [CRD42022320665].